Ethnicity Effects in Graduates' Résumé Content. Issue 3 (29th February 2012) - Hiemstra, Annemarie M.F.; Derous, Eva; Serlie, Alec W.; Born, Marise P.
<x xml:space="preserve">Abstract</x> Highly educated ethnic minority entrants in Western countries need more time to find a job compared to their Western ethnic majority counterparts. The present study examined whether this differential job access is partly explained by the way ethnic minorities present themselves in their résumés. To this end, a comparison between 100 non‐Western ethnic minority graduate résumés and 100 native Western ethnic majority graduate résumés was made. Non‐Western ethnic minorities score significantly lower on reported organisational internships, leadership experiences, and extracurricular activities. Although most effects were small, these differences in résumé content resulted in lower job suitability ratings for non‐Western ethnic minorities compared to Western ethnic majorities, as judged by professional recruiters/HR experts. Résumé presentation (e.g. layout and grammar) also was a significant predictor of job suitability ratings, but no ethnicity effects were found in these résumé characteristics. Because rater effects which may be related to hiring discrimination were controlled for, it can be concluded that the reported human capital in résumés can explain differential job access of ethnic minority compared to ethnic majority graduates. Theoretical and practical implications for assessing ethnic minorities upon organisational entry are discussed.